Удосконалення характеристик автономного факельного підігрівача на двигуні 5ТДФ - Серпухов, Олександр Васильович; Коритченко, Костянтин Володимирович; Бізонич, Д. В. (НТУ "ХПІ", 2015)
В статье представлены результаты экспериментальной проверки автономного факельного подогревателя с усовершенствованной электрической разрядной системой зажигания. Исследовано время задержки воспламенения струи дизельного топлива в АФП и температура подогретого воздушного заряда в контрольных точках двигателя.

The results of experimental verification of features of autonomous flame heater with the improved electrical ignition system on the engine 5TDF are presented in the article. It is investigated the time of delay of self-ignition of diesel fuel in AFP and temperature of warmed-up air charge in the control points of engine.
Improvement of features of autonomous flame heater on the engine 5TDF
Keywords: АФП; спалахування; запалювання; камера згорання; потужність іскрового розряду; electrical ignition system; diesel fuel; AFP